Eruptive xanthomas as a marker for metabolic disorders: A specific form of xanthoma that reflects hypertriglyceridemia. Issue 4 (21st April 2022) - Ohtaki, Sohichiroh; Ashida, Kenji; Matsuo, Yuko; Moritaka, Kanoko; Iwata, Shimpei; Nagayama, Ayako; Kawaguchi, Aya; Koga, Hiroshi; Yoshinobu, Satoko; Hasuzawa, Nao; Motomura, Seiichi; Akiba, Jun; et al.
Abstract: Eruptive xanthomas are skin manifestations associated with hypertriglyceridemia. Accordingly, the improvement of hypertriglyceridemia can ameliorate this condition. We report a case of a patient with type 2 diabetes mellitus who was diagnosed with this skin lesion. Clinicians should be aware that eruptive xanthomas could indicate metabolic disorders associated with atherosclerosis. Abstract : Eruptive xanthomas are associated with hypertriglyceridemia due to dysregulated lipid and glucose metabolism. Clinicians should not overlook eruptive xanthomas as possible indicators of metabolic disorders associated with cardiovascular disease.